2002
DOI: 10.1300/j013v35n02_09
|View full text |Cite
|
Sign up to set email alerts
|

Abused Patient's Attitudes About Mandatory Reporting of Intimate Partner Abuse Injuries to Police

Abstract: Despite broad support among abused women for medical clinician reporting of intimate partner abuse injuries to police, most women do not support mandatory reporting requirements that do not allow for consideration of the abused patients' wishes. More research is needed to ascertain whether the benefits of mandatory reporting outweigh the risks to those intended to benefit from the law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…For example, in one emergency room study in California, 55.7% of women in the study supported mandatory reporting (Rodriguez, McLoughlin, Nah, & Campbell, 2001). However, Rodriguez et al (2002) led a study with 358 women in California and found that while most women supported some form of reporting to police, the majority (68%) did not endorse a domestic violence reporting mandate if it was against the wishes of a patient. Coulter and Chez (1997) conducted a study with 45 women receiving services in a community outreach program for victims of domestic violence.…”
Section: Evaluation Of Mandatory Reporting Laws On Victims Of Domestic Violencementioning
confidence: 99%
“…For example, in one emergency room study in California, 55.7% of women in the study supported mandatory reporting (Rodriguez, McLoughlin, Nah, & Campbell, 2001). However, Rodriguez et al (2002) led a study with 358 women in California and found that while most women supported some form of reporting to police, the majority (68%) did not endorse a domestic violence reporting mandate if it was against the wishes of a patient. Coulter and Chez (1997) conducted a study with 45 women receiving services in a community outreach program for victims of domestic violence.…”
Section: Evaluation Of Mandatory Reporting Laws On Victims Of Domestic Violencementioning
confidence: 99%
“…Mandatory reporting, although originally enacted to serve the single purpose of protecting vulnerable children from abuse, continues to be considered for ever expanding purposes including: elder abuse (Bergeron & Gray, 2003; Canadian Network for the Prevention of Elder Abuse, 2008; Dakin, 2004;Stratton & Yamasaki, 2003;Wei & Herbers, 2004), work place harassment (Government of Ontario, 2009;Ministry of Labour, Ontario Government, 2010), domestic violence (Bledsoe, Yankeelov, Barbee, & Antle, 2004;Edleson et al, 2006;Rodriguez, Sheldon, & Rao, 2002;Sachs, Koziol-McLain, Glass, Webster, & Campbell, 2002;C. M. Sullivan & Hagen, 2005), school bullying (Duncan-Daston, 2003;Talaga, 2009) and sexual relations between professional and past client (McPhedran et al, November 25, 1991;Ontario College of Social Workers and Social Service Workers., 2000;Pope, 1994).…”
Section: Subsequent Uses Of the Mandatory Reporting Protocolmentioning
confidence: 99%
“…While support for universal IPV screening is very high among women with and without a history of abuse, concerns have been raised that mandatory reporting affects patient autonomy and confidentiality, may deter victims from disclosing IPV or seeking medical care, and may possibly increase the risk of retaliation [104,135,136,139,140]. In one state with mandatory reporting, 12% of women attending an inner-city emergency department indicated that, with mandatory reporting, they would be less likely to seek care for an IPV-related injury while 27% said they would be more likely to seek care [141].…”
Section: Mandatory Reportingmentioning
confidence: 99%
“…In one state with mandatory reporting, 12% of women attending an inner-city emergency department indicated that, with mandatory reporting, they would be less likely to seek care for an IPV-related injury while 27% said they would be more likely to seek care [141]. Studies show that survivors of IPV have very high support for universal screening and physician reporting with patient approval, but have mixed support for mandatory reporting with 44% to 68% of women with a history of abuse opposing mandatory reporting that does not allow for consideration of patients wishes [139,140]. In states with mandatory reporting, if a patient objects, it is important to ask why, to try to address any concerns, and to relay the patient's objections and reasons to the authorities.…”
Section: Mandatory Reportingmentioning
confidence: 99%